Potensi Penggunaan Agregat RAP (Reclaimed Asphalt Pavement) Terhadap Campuran SMA (Stone Matrix Asphalt) - Edi Yusuf Adiman; Benny Hamdi Rhoma Putra; Muhammad Rilly Aka Yogi (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2023)
The advantage of using RAP (Reclaimed Asphalt Pavement) materials in road pavement has economic and environmental benefits. The RAP materials are used in the form of bitumen only, aggregates only, or both of them. This study proposes to determine the potential of RAP aggregate as a material for an SMA mixture. The variation of RAP aggregate in this study is based on function use, the nominal maximum aggregate size (NMAS), and minimum thickness of use from the results of the RAP aggregate test. The method in the manufacture and testing of specimens using the Marshall method. From the results of the testing and analysis of the RAP aggregate, the variations in RAP aggregate used in this study were 0%, 33%, and 47%. The results of the marshall test on the SMA mixture, the optimum bitumen content (OBC) of the RAP 0% was 6.23%, and the RAP 33% was 6.1%, while the RAP 47% OBC could not be determined because it did not fulfill standard requirements of the Marshall based on the value of VMA and VITM. From these results, the potential use of RAP aggregate for SMA mixtures is 33%. This value is the percentage of the RAP aggregate potential in the SMA mixture that fulfills the standard requirements of the Marshall and testing aggregate.